Bi‐Directional Energy Cascades in the Pacific Ocean From Equator to Subarctic Gyre. Issue 8 (22nd April 2022) - Qiu, Bo; Nakano, Toshiya; Chen, Shuiming; Klein, Patrice
Abstract: Ocean circulation receives its energy input at basin scales while dissipates at microscopic mixing scale. How this energy is transferred across different lengthscales is of paramount importance for understanding the ocean circulation equilibration and variability. Advancement in high‐resolution numerical simulations in recent years has significantly improved our understanding of kinetic energy (KE) cascades from basin to kilometer scales, although observational evidence to verify the simulated processes remains limited. Using repeat ship‐board velocity measurements along 165°E across the equatorial, subtropical and subarctic Pacific Ocean, we show that the length scale separating the inverse and forward cascades, L S, falls in the 8 ∼ 300 km range and it does not scale straightforwardly with the baroclinic deformation radius. Balanced and unbalanced oceanic motions co‐exist in this range but contribute oppositely to the directional energy cascades. L S is observed to depend on the relative strengths of these motions, as well as by their interaction. Plain Language Summary: This paper investigates how nonlinear interactions in the turbulent upper ocean transport kinetic energy (KE) across different spatial scales. This investigation is important because the energy input that drives the ocean circulation has scales at tens of thousand kilometers, whereas the oceanic mixing and dissipation take place below the centimeter scales. How oceanic KE is transported from one scale to another is neither fully understood nor adequately observed, and this is particularly true in the oceanic meso‐submesoscales in the 1 ∼ 300 km range. By using repeat shipboard Acoustic Doppler Current Profiler surveys from 2004 to 2020 in the western Pacific Ocean, we examined the cross‐scale KE transfers in dynamically different regimes of tropics, subtropics and high latitudes. We found that the KE can transfer both up‐scales and down‐scales due to the co‐existence of balanced geostrophic motions and unbalanced wave motions. The length scale that separates the bi‐directional KE transfers is geographically dependent. It is controlled by the relative strengths of co‐existing balanced and unbalanced motions, as well as by how the unbalanced wave motions are dynamically generated. Key Points: Nonlinear interaction in upper ocean transfers kinetic energy both up‐ and down‐scales Upper ocean balance and unbalanced motions contribute oppositely to energy cascade Bi‐directional energy cascade depends on relative importance of balanced versus unbalanced motions and characteristics of the unbalanced motions